Review of Caribbean economic and social performance in the 1980s and 1990s (ECLAC Port of SpainTT, 1999)
Reviews the social and economic performance of Caribbean countries in the 1980s and the 1990s and highlights a few of the changes which have taken place.
Keywords: ECONOMIC PERFORMANCE